Genotypes and phenotypes in a Wolbachia-ant symbiosis - Crystal L. Frost; Rowena Mitchell; Judith Elizabeth Smith; William O.H. Hughes (PeerJ, 2024)
The fitness effects of overt parasites, and host resistance to them, are well documented. Most symbionts, however, are more covert and their interactions with their hosts are less well understood. Wolbachia, an intracellular symbiont of insects, is particularly interesting because it is thought to be unaffected by the host immune response and to have fitness effects mostly focussed on sex ratio manipulation. Here, we use quantitative PCR to investigate whether host genotype affects Wolbachia infection density in the leaf-cutting ant Acromyrmex echinatior, and whether Wolbachia infection density may affect host morphology or caste determination. We found significant differences between host colonies in the density of Wolbachia infections, and also smaller intracolonial differences in infection density between host patrilines. However, the density of Wolbachia infections did not appear to affect the morphology of adult queens or likelihood of ants developing as queens. The results suggest that both host genotype and environment influence the host-Wolbachia relationship, but that Wolbachia infections carry little or no physiological effect on the development of larvae in this system.